VEGF‐C Induces Lymphangiogenesis and Angiogenesis in the Rat Mesentery Culture Model. (August 2014) - Sweat, Richard S.; Sloas, David C.; Murfee, Walter L.
Abstract Objective Lymphatic and blood microvascular systems are critical for tissue function. Insights into the coordination of both systems can be gained by investigating the relationships between lymphangiogenesis and angiogenesis. Recently, our laboratory established the rat mesentery culture model as a novel tool to investigate multicellular interactions during angiogenesis in an intact microvascular network scenario. The objective of this study was to determine whether the rat mesentery culture model can be used to study lymphangiogenesis. Methods Mesenteric tissue windows were harvested from adult male Wistar rats and cultured for three or five days in either serum‐free MEM or MEM supplemented with VEGF‐C. Tissues were immunolabeled for PECAM and LYVE‐1 to identify blood and lymphatic endothelial cells, respectively. Tissues selected randomly from those containing vascular networks were quantified for angiogenesis and lymphangiogenesis. Results VEGF‐C treatment resulted in an increase in the density of blood vessel sprouting compared to controls by day 3. By day 5, lymphatic sprouting was increased compared to controls. Conclusions These results are consistent with in vivo findings that lymphangiogenesis lags angiogenesis after chronic stimulation and establish a tool for investigating the interrelationships between lymphangiogenesis and angiogenesis in a multisystem microvascular environment.